Effect of temperature and diet (starch and fiber) on embryonic development, energy metabolism and growth of red-footed tortoise (Chelonoidis carbonaria) - Mendoza Yengle, Pierina Jocelyn (2021)
Descargue el texto completo en el repositorio institucional de la Universidad Estadual Paulista: http://hdl.handle.net/11449/204639